The farmer's small fruit plantation - Edwards, Mary Josephine (My University, 1905)
Introduction: In treating this subject, it is the object to speak not of commercial plantings, but of the plantings now made on hundreds of American farms, and which should be made on hundreds more, which are primarily for the owners private use and enjoyment. For this reason it will be unnecessary, in fact would be inappropriate, to treat, in detail of the history or botany of the plants to be considered. The average man who grows a strawberry on a farm today cares much more for the flavor and size of that berry and the conditions of soil and culture which will produce perfection in these lines than he does for the study of the exact leaf characteristics that will determine the botanical relation of one species to another. He is interested not in the past, in the history of the development, but in the present and the future development of the plant. For this reason we will begin with the soil and climatic conditions required for small fruit culture on a Kansas farm today. It may be well to state the general classes of plants of which we intend to speak. Besides the so-called bush fruits, which are composed of the Brambles - including Red and Black Raspberries, Blackberries and Dewberries, and the Groselles - including gooseberries and Currents -, it is the intention to treat also of the strawberry and Grape. This classification will then include all principal fruits with exception of tree fruits. These will be treated in logical order but will nearly simulate the succession of fruit throughout the season.
Citation: Edwards, Mary Josephine. The farmer's small fruit plantation. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Soil Preparation; Fertilizer; Barieties of Berries; Theses